Sufi Rituals in Suluk as a Mechanism for Internalizing Tolerance Values Character Education in Pesantren - Muhammad Jakfar Al Arof; Saifullah; Ahmad Marzuki (Journal of Contemporary Islamic Education, 2026)
This study examines the internalization of tolerance values through the Sufi ritual of suluk (spiritual retreat) at Pondok Pesantren Darut Taqwa Mojokerto. While character education is frequently articulated within normative and instructional frameworks, it often overlooks the lived and experiential dimensions through which values are actually formed and sustained. Addressing this gap, the present study highlights how collective spiritual practices function as socio-pedagogical mechanisms that enable the embodiment of tolerance through shared rituals, social interaction, and spiritual discipline. Employing a qualitative case study design, data were collected through participatory observation, in-depth interviews, and document analysis. The findings reveal that the internalization process unfolds through three interconnected stages: symbolic transformation, habituation and normative consolidation, and affective internalization leading to social reproduction. The ritual structure symbolically conveys egalitarian values through non-hierarchical arrangements and collective participation. Repetitive engagement fosters habituation, which strengthens moral awareness and commitment. Furthermore, shared spiritual experiences generate affective solidarity, mediating the transformation of tolerance values into stable character dispositions manifested in everyday social interactions. This study proposes a ritual-based model of value internalization that integrates symbolic, habituative, and affective dimensions within a unified process. It argues that tolerance is not merely transmitted through moral instruction but is cultivated through embodied collective experience. The findings underscore the potential of Sufi ritual practices as effective non-formal educational mechanisms for reinforcing social cohesion in multicultural contexts.